2004
DOI: 10.1080/15389580490510507
|View full text |Cite
|
Sign up to set email alerts
|

WalkSafe: A School-Based Pedestrian Safety Intervention Program

Abstract: Objective: To evaluate the effectiveness of the WalkSafe program, an elementary school-based pedestrian safety program in a single high-risk district in Miami-Dade County.Methods: Sixteen elementary schools were identified in a single high-risk district and enrolled in a one-year study. All schools implemented the WalkSafe program on the last week of January 2003. A pre, post, and three-month post testing of pedestrian safety knowledge was conducted. An observational component was also implemented at four scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 6 publications
2
26
0
4
Order By: Relevance
“…1,32 If we know the ages and skill acquisition of children, the application of prevention measures becomes easier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,32 If we know the ages and skill acquisition of children, the application of prevention measures becomes easier.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the number of traffic accidents, and consequently in the number of deaths and injured individuals, is still a challenge 1,32,33 and, for enhanced efficiency, some aspects should be emphasized:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements were more consistent for grades K-3 than for 4 and 5. Actual in-traffic behaviors were also reportedly improved in the short term, but did not hold up at 3 months after the program, and no comparison group was used (Hotz et al, 2004;Hotz et al, 2009). Barton, Schwebel, and Morrongiello (2007) also reported that children crossed a road more safely immediately following a brief pedestrian safety training that included instruction followed by practice crossings on a pretend road.…”
Section: Effectivenessmentioning
confidence: 99%
“…A recent study found a preschool education program effective in improving appropriate restraint use among 3-to 5-year-old children, while a multifaceted community approach which included a school intervention also improved restraint use (21,22). Similarly, schoolbased interventions have been successful with safety topics including water and pedestrian safety (19,(23)(24)(25)(26)(27).…”
mentioning
confidence: 99%